Structural Components of Lifestyle and Beyond: The Case of Hungary - Keller, Tamás; Róbert, Péter (Studies of Transition States and Societies, 2011)
This paper deals with the question of when and how lifestyle and its components are important in social stratiﬁ cation. There is considerable consensus among scholars about the structure of the society being a consequence of hierarchical dimensions like occupation, income, or wealth. Some thirty years ago, largely based on Bourdieu’s “Distinction”, a new paradigm emerged highlighting the lifestyle components and the value-oriented cultural and material consumption in stratiﬁ cation. The idea reﬂ ects the empirical ﬁ nding that inequality between social classes has largely decreased, giving priority to horizontal lifestyle diﬀ erentiation instead of vertical inequality dimensions. From a theoretical viewpoint, a challenge in the approach is ﬁ nding out to what extent lifestyle typology is of a non-vertical character in reality. This social determination of lifestyle is investigated for Hungary when comparing an occupation-based typology with a consumption-based one. On the one hand, results reveal that the eﬀ ects of structural components on social status are stronger than those of lifestyle. On the other hand, lifestyle turns out to be less independent of social position and the top and bottom levels of the lifestyle typology are particularly predictable by structural measures.